2016
DOI: 10.1149/2.0611608jes
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Sputtered Al-Doped ZnO Seed Layer on the Morphological, Structural and Optical Properties of Electrochemically Grown ZnO Nanorod Arrays

Abstract: The effect of both a RF sputtered Al-doped ZnO (AZO) thin film seed layer onto a FTO/glass substrate and its growth time onto the morphological, structural and optical properties of the resulting electrochemically grown ZnO nanorod arrays (NRAs) have been studied. ZnO NRs grown onto the different AZO seed layers exhibit smaller mean diameter and length than those grown onto a bare FTO/glass substrate, but ZnO NR density presents an opposite behavior, by using an AZO seed layer ZnO nanorod density can be increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 68 publications
(125 reference statements)
0
24
0
Order By: Relevance
“…The depth profiles of Al concentration in AZO thin films were determined by SIMS measurements. The textures of the films were characterized by measurements of wide-range out-of-plane reciprocal space maps [ 14 , 16 , 17 , 44 ] and pole figures [ 14 , 16 , 17 , 45 , 46 , 47 , 48 ] using the SmartLab XRD system (Rigaku Corp, Tokyo, Japan) equipped with a PILATUS 100 K/R two-dimensional X-ray detector using Cu-K radiation (wavelength λ = 0.15418 nm; weighted average of Cu-Kα 1 λ = 0.154059 nm/Cu-Kα 2 λ = 0.15444 nm with an intensity ratio of 2:1). The width of the X-ray beam on the samples is 10 mm during XRD measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The depth profiles of Al concentration in AZO thin films were determined by SIMS measurements. The textures of the films were characterized by measurements of wide-range out-of-plane reciprocal space maps [ 14 , 16 , 17 , 44 ] and pole figures [ 14 , 16 , 17 , 45 , 46 , 47 , 48 ] using the SmartLab XRD system (Rigaku Corp, Tokyo, Japan) equipped with a PILATUS 100 K/R two-dimensional X-ray detector using Cu-K radiation (wavelength λ = 0.15418 nm; weighted average of Cu-Kα 1 λ = 0.154059 nm/Cu-Kα 2 λ = 0.15444 nm with an intensity ratio of 2:1). The width of the X-ray beam on the samples is 10 mm during XRD measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The SP‐ZnO transmittance spectra also shows the typical sharp direct‐like absorption edge of ZnO thin films located at 380 nm . The SP‐ZnO/NP‐ZnO spectrum (dot‐dashed curve) also presents the ZnO absorption edge previously described and a smooth monotonous increment for longer wavelengths caused in the light scattering properties of the sample . The transmittance of the buffer layer (dotted curve) shows an absorption edge located at 490 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, both samples with NP (SC2 and SC3) have a greater IPCE in the visible region. This may be due to the light scattering capability of the NP . The IPCE integrated short circuit current density was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…These seed-layers could play the role of growth centres during deposition of metal oxides and thus can affect the structural properties of these films [7]. Later it was shown that this approach can be used in the formation of various metal oxide films by the methods of sol-gel technology, electrochemical deposition, aerosol-assisted CVD, chemical bath deposition and so on [8][9][10][11][12]. It was shown that the pre-coating of glass and silicon substrates by seed-layers affected texturing and crystallinity and was crucial for the formation of metal oxides with controlled properties.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the possibilities of the proposed approach, we use SnO 2 and In 2 O 3 , which relate to materials promising for a wide range of applications from catalysis and displays to gas sensors [16]. Previously, studies in this area were mainly devoted to ZnO [8,9,12].…”
Section: Introductionmentioning
confidence: 99%